Influence of the specific heat capacity of the raw material fermented in a biogas reactor on the heat distribution - Spodoba М.О.; Spodoba О. О. (Energy and Automation, 2026)
Every year, the use of biogas technologies gives impetus to the development of new methods of handling accumulated waste from agricultural and household facilities. Therefore, the current issue is to reduce energy costs for maintaining the microclimate of fermentation, with the maximum possible formation of biogas from a certain type of raw material. Physico-chemical parameters have a significant impact on the fermentation of raw materials and energy costs. The purpose of the work is to analyze the impact of the specific heat capacity of the raw material fermented in a biogas reactor on the change in the Prandtl criterion and energy costs for heating. The results of theoretical studies are presented, during which the impact of the range of specific heat capacity of raw materials from 1000 to 4000 J/(kg 0C) on energy costs was analyzed The result is graphical dependences that describe the change in the heat transfer coefficient and heat transfer from the heating device to the raw material, the change in the Prandtl and Reynolds criteria depending on the change in the specific heat capacity of the raw material and the speed of rotation of the mixing device. The percentage change in the Reynolds criterion, heat transfer coefficients and heat transfer when changing the speed of rotation of the mixing device is established. It is established that the change in the Prandtl criterion depending on the change in the specific heat capacity of the raw material occurs according to a linear law. The use of the obtained results in combination with previous studies concerning the influence of physicochemical parameters on energy consumption gives an impetus towards establishing a rational speed of rotation of the mixing device from the point of view of energy consumption. Recieved 2025-11-27 Recieved 2026-01-19 Accepted 2026-02-11